Evaluation of the practical application of students of the Lebanese Lebanese University and the University of Salahaddin In basic education schools - األستاذ المساعد الدكتور محمد صديق خؤشناو; المدرسة المساعدة نضال عبد الحافظ طاهر (QALAAI ZANIST SCIENTIFIC JOURNAL, 2018)
The studyevaluates and compares the performance of the "practitioners students” in both the Lebanese French University, and SalahaddinUniversity, in the following dimensions: Application of Scientific Knowledge and Teaching Skills, Following Up practitioners students in Basic Education Schools, and the existence of significant differences at level 0.05 between these two universities. A questionnaire for collecting datawas designed, after verifying its validity and reliability was applied in basic education schools Erbil,.Likert equation was used to determine the degree of performance in both Universities, ALPHA KRONBACH coefficient for determining the degree of reliability, and ANOVA to determine the existence of significant differences between the performances of these two Universities. The findings shown superiority of the Lebanese French University in dimension of” follow-up of practitioner's students”. Performance of students in the dimension of “application knowledge and teaching skills” in both Universities was highscore (2.68).